Comparison of Molecular Variation in Two Regions of The Cytochrome C Oxidase Subunit I of Anopheles triannulus from Colombia (2021)
Two Anopheles triannulatus genetic lineages were previously detected, differentially distributed at northwest (NW lineage) and southeast (SE lineage) Colombia. These lineages could differ in their biology and ability to transmit malaria. Although the lineages were molecularly defined using the 3' Cytochrome c oxidase subunit 1 (cox1 or COI) and the internal transcribed spacer 2-ITS2 sequences, a different cox1 region, the 5′ end, has been widely used for species identification in dipterans and may be used in differentiating these lineages. This study compared the variation between two cox1 gene regions, the 3' (Lunt) and 5' (Folmer) ends, in An. triannulatus from Colombia in order to evaluate their accuracy for identification at the lineage level. Results showed that the cox1 Folmer fragment would not facilitate detection of lineages in An. triannulatus, while cox1 Lunt allowed separation of specimens into the two perilously detected lineages, NW and SE.